Transcriptomics and metabolomics reveal the mechanism of cognitive impairment induced by long-term selenium deficiency in miceMendeley Data - Wanpeng Cheng; Yani Wang; Peiyue Sa; Luyun Liang; Lantian Zhang; Guangyan Shen; Jincheng Luo; Mengdi Li (Ecotoxicology and Environmental Safety)
As the aging population increases, cognitive impairment is emerging as a growing health issue worldwide. Low selenium status has been reported to correlate with cognitive decline in older adults. Nonetheless, the impact of prolonged selenium deficiency on cognitive function in adult mice and the underlying mechanisms remain poorly understood. In this research, male C57BL/6 J mice were given either a normal diet (0.2 mg/kg Se) or a selenium-deficient diet (0.02 mg/kg Se) for 24 weeks to evaluate the impact of long-term selenium insufficiency on their cognitive abilities. We performed hippocampus transcriptome sequencing, real-time PCR, Golgi-Cox staining, transmission electron microscopy, western blotting, and untargeted brain metabolomics to uncover the underlying regulatory mechanism. We found that chronic selenium deficiency impaired the capabilities of object recognition, spatial memory, and self-caring in mice, and disrupted the expression of key genes related to cognitive behavior, dendrite morphogenesis, and synaptic plasticity. Additionally, prolonged selenium deficiency compromised neurite integrity, decreased dendritic spine density, impaired synaptic ultrastructure, and reduced synaptic protein expression. Brain metabolomics revealed that differential metabolites (methylmalonic acid, N-acetyl-1-aspartylglutamic acid, and S-adenosylmethionine) may be involved in the process of cognitive impairment. These findings suggest that perturbation in cognition-related transcriptome profiles, lesions in neurites and synapses, and remodeling of the brain metabolic pattern are involved in the cognitive impairment induced by long-term selenium deficiency. Our study offers a new perspective on the pathogenesis of cognitive impairment, highlighting the critical role of selenium supplementation in maintaining healthy cognitive function.